The Rational Appropriateness of Group-Based Pride - Salmela, Mikko; Sullivan, Gavin Brent (Frontiers in Psychology, 2022)
This article seeks to analyse the conditions in which group-based pride is rationally appropriate. We distinguish, following D´Arms and Jacobson (2000), between the shape and size of an emotion. For the appropriate shape of group-based pride, we suggest two criteria: the distinction between group-based pride and group-based hubris (Sullivan & Hollway, 2014), and between we-mode and I-mode sociality (Tuomela, 2007). While group-based hubris is inappropriate irrespective of its mode due to the arrogant, antagonistic, and other-derogating character of this emotion, group-based pride in the we-mode is appropriate in terms of shape if it is felt over an achievement to which the group members collectively committed themselves. For the same reason, members of I-mode groups can feel appropriately proud of the achievement of their group if they have collectively contributed to it. Instead, group-based pride by mere private identification with a successful group can be rationally appropriate if it manifests the person´s reduced-agency ideal (Brady, 2017) and is also part of a coherent pattern of rationally interconnected emotions focused on the same ideal (Helm, 2001). Moreover, we suggest that pride in the success of one's family member or a close friend is typically felt over the rise of social status that one group member's success grants to the group. However, social status cannot be valued for its own sake as this undermines the values upon which social status is founded. Instead, direct or indirect causal contribution to the success of one´s child, friend, or student can warrant group-based pride, which may be justified on the basis of shared values without causal contribution as well. Finally, regarding the size of group-based pride, members of we-mode groups are warranted to experience and express more intense pride than members of I-mode groups. Moreover, the proper intensity of this emotion depends on the particular other(s) to whom the expression is directed. Finally, criteria of appropriate size don´t apply to shared group-based pride as sharing increases the intensity of emotion by default.